Modeling and Analysis of a Multi-Degree-of-Freedom Micro-Vibration Simulator - Xiaoming Wang; Zhenbang Xu; Shuai He; Qingwen Wu; Hang Li; Yaping Zhao; Lei He (Shock and Vibration)
To reproduce the disturbance forces and moments generated by the reaction/momentum wheel assembly, a multi-degree-of-freedom micro-vibration simulator is proposed. This can be used in the ground vibration experiments of an optical payload replacing the real action/momentum wheel assembly. First, the detailed structure of the micro-vibration simulator is introduced. Then, the complete system kinematic and dynamic models of the micro-vibration simulator are derived. In addition, the disturbance forces and moments produced by the micro-vibration simulator are calculated. Finally, the normal mode analysis and a cosimulation are adopted to verify the validity of this method. The analysis and simulation results show that the micro-vibration simulator can exactly reproduce the disturbance forces and moments with different amplitudes and different frequency ranges.